The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fphar.2018.00349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytochemically Characterized Extracts From Syringa vulgaris and Isolated Secoiridoids on Mediators of Inflammation in a Human Neutrophil Model

Abstract: Aim of the study: The aim of the present study was to investigate the effects of phytochemically characterized extracts connected with the traditional use (infusions and ethanolic extracts) of different parts of Syringa vulgaris (common lilac) on the pro-inflammatory functions of neutrophils. Active compounds were isolated from the most promising extract(s) using bioassay-guided fractionation, and their activity and molecular mechanisms of action were determined.Methods: The extracts were characterized using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…Recently, Wozniak et al. demonstrated that oleuropein decreased p38 MAPK, ERK1/2, and JNK and prevented the translocation of NF‐KB from cytosol to nucleus which is critical for the activation of NF‐KB . Castejon et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wozniak et al. demonstrated that oleuropein decreased p38 MAPK, ERK1/2, and JNK and prevented the translocation of NF‐KB from cytosol to nucleus which is critical for the activation of NF‐KB . Castejon et al.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-activated neutrophils cause phosphorylation of p38 MAPK, ERK, and JNK and translocation of NF-KB 41. Recently, Wozniak et al demonstrated that oleuropein decreased p38 MAPK, ERK1/2, and JNK and prevented the translocation of NF-KB from cytosol to nucleus which is critical for the activation of NF-KB 42. Castejon et al also supported these results demonstrat-, and MMP-13 expressions 44.…”
mentioning
confidence: 85%
“…UV spectra were recorded in the range 200–400 nm. Compounds were identified by comparing their retention time and UV‐visible and mass spectra with those obtained from standard compounds isolated previously from other Oleaceae family members and/or tentatively identified by comparison with literature information.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral venous blood was taken from healthy human donors (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years old) at the Warsaw Blood Donation Centre. The donors did not smoke or take any medications and were clinically recognised to be healthy.…”
Section: Isolation Of Human Neutrophilsmentioning
confidence: 99%
“…Mit späterer handschriftlicher Ergänzung "Hartriegel -Ligustrum vulgare L." Exemplar der Universität Straßburg Porträt Thieme Phytochemie Zur Klärung der Frage nach Wirkung und Wirksamkeit dieser historischen Droge ist zunächst eine phytochemische Bestandsaufnahme notwendig. Mit diesem Ergebnis, das auf entzündungshemmende Wirkungen verweist, und den vielfältig in der Literatur zu findenden anti-inflammatorischen Effekten von Oleuropein, das u. a. ein aktiver Hemmer von NF-κB in humanen Neutrophilen ist[13], lassen sich die Indikatio-…”
unclassified